Identify Characteristics Patient Chronic Kidney Failure at Dr. R. Soetijono Hospital Blora - Heru Purnomo; Mu'awanah; Pambayun Sugeng Uripno (CV. Get Press Indonesia, 2024)
Background research based on the Global Burden of Disease (GBD) study shows that chronic kidney failure has been shown to be the main cause of death in the world. Kidney failure is one of the four diseases that can cause a high financial burden. Purposes is to know description of a case of chronic renal failureat Dr. R. Soetijono Hospital Blora for the period January 2021 to December 2022. Research methods used is the Retrospective Descriptive method using secondary data in the form of medical records / patient status stored in the Medical Records section of Dr. R. Soetijono Hospital Blora, period January 2021 to December 2022. Research result in the period January 2021 to December 2022, there were 221 cases of Chronic Kidney Failure, most of whom were adults and seniors, the gender was predominantly female, which is suspected to be the influence of kidney estrogen, as for the factors causing Chronic Kidney Failure, most of the patients had a history of Diabetes Mellitus with Hemodialysis therapy, and There was an increase in the number of cases by 27% from 2021 to 2022. Implications: The increase in the number of cases of Chronic Kidney Failure will have an impact on the readiness of health services in preparing facilities, resources, costs and technology to overcome problems that occur in CKF patients. Conclusion research that promotive and preventive efforts are very necessary in dealing with cases of Chronic Kidney Failure in adults with a history of Diabetes Mellitus.